Augmentation of hepatitis C virus‐specific immunity and sustained virologic response. Issue 9 (4th May 2017) - Shrivastava, S.; Wilson, E.; Poonia, B.; Tang, L.; Osinusi, A.; Kohli, A.; Kottilil, S.
Summary: Treatment for chronic hepatitis C virus (HCV) infection has rapidly evolved into interferon‐free directly acting antiviral regimens (DAA) that result in high sustained virologic response. DAAs primarily work by suppressing HCV replication and rely less on the immune system than interferon‐based therapies. However, it is unclear whether the immune system recovers with suppression of HCV replication and contributes to HCV clearance with DAA therapy. We previously demonstrated HCV clearance is associated with increased HCV‐specific immunity in CHCV‐GT‐1‐infected patients during treatment with sofosbuvir (SOF)+ribavirin (RBV). Here, we aimed to analyse changes in HCV‐specific immunological responses associated with viral clearance with combination DAA therapy of SOF+ledipasvir (LDV) for 12 weeks in CHCV‐GT1 (N=14) patients who relapsed without augmentation of HCV‐specific immunity during treatment with SOF+RBV. Phenotypic and functional changes within the T‐cell compartment of PBMCs pre‐ and post‐treatment were analysed. Retreatment of relapsers with LDV/SOF resulted in all patients attaining SVR12 . Suppression of HCV was associated with a decline in T‐cell exhaustion markers (CD57; Tim3; PD1) along with augmented of HCV‐specific T‐cell IFN‐gamma responses post‐treatment. Addition of LDV to SOF was associated with augmentation of HCV‐specific immunity and SVR in patients who previously failed SOF+RBV therapy without increased immunity. These findings demonstrate a novel effect of DAA in inducing host immune responses to aid HCV clearance and achieve SVR.